Quand les acteurs faibles et absents s’immiscent dans la négociation environnementale - Léa Sebastien (Territoire en Mouvement, 2011)
Ecological disturbances force us to inquire, at both global and local levels : how to live together ? or more precisely, how to decide together ? On this aspect, we show that negotiation theories reveal their weaknesses when confronted to absent actors and weak actors, two entities playing an important role in environmental issues. In order to facilitate an environmental negotiation in a multi-actor context, we have elaborated a model entitled : the Actor in 4 Dimensions (A4D). Tested on various case studies of which 2 in France (Adour, Forez), this conceptual model originates from a multidisciplinary approach and aims at apprehending the stakeholders’ dynamics on a territory by studying the interactions between social relations and environmental practices. We can identify weak and absent actors on an area and we highlight the fact that a consensus among strong actors can lead to environmental degradations. We also present 4 types of attitudes toward the idea of participation. The objective is to reach an environmental negotiation which would be handled by a mediator who could bring to light the stakes of weak and absent actors : a working basis for the implementation of approaches aiming integrated and participative natural resource management.